Heat transfer evaluation of natural convection outside the condenser in Passive Residual Heat Removal System of Molten Salt Reactor. (December 2021) - Tao, Ding; Guang-liang, Yang; Guang-ming, Fan; Chun-Ping, Tian; Zhao-Ming, Meng; Kal-lun, Chen; Chang-Qi, Yan; Hong-li, Chen
Abstract: A full scale water-cooled Passive Residual Heat Removal System was designed and built for a 2 MW Molten Salt Reactor. In the process of heating the water tank, the heat transfer characteristics of the condenser in the system had an important impact on the temperature distribution and the development of thermal stratification in the water tank. Therefore, the heat transfer characteristics of the condenser at single-phase natural convection stage need to be experimentally researched and theoretically analyzed. Aiming at the condenser in the system, a series of experiments were carried out. Considering the influence of tube bundle effect on natural convection heat transfer, a set of theories using hydraulic diameter as characteristic length were put forward and applied to analyze the experimental results, which indicated the good agreement with the previous correlations consequently. This study can provide theoretical feasibility and experimental reference for the design of commercial molten salt reactor system in the future.